Pengaruh Flash Sale dan Live Streaming terhadap Perilaku Impulsive Buying pada Marketplace Shopee di Kabupaten Purworejo - Aisya Putri Sintowati; Anes Arini; Anna Probowati (Prospect : Jurnal Manajemen dan Akuntansi, 2025)
This research aims to find out whether there is a positive and significant influence between flash sales and live streaming on impulsive buying behavior on the Shopee marketplace in Purworejo Regency. Data collection was carried out using observation techniques, interviews, questionnaires, literature studies and documentation. The population of this research is Shopee consumers in the Purworejo Regency area whose number is unknown and can be said to be in the infinite category. The research sample was 96 people using purposive sampling technique. The data obtained were analyzed using techniques: validity test, reliability test, multiple linear regression, coefficient of determination, t test, and f test. Multiple regression analysis produces the equation Y = 9.271 + 0.477 X1 + (-0.154) X2 + e. Hypothesis testing (t test) shows that there is a positive and significant influence between flash sales on impulsive buying behavior on the Shopee marketplace and there is no positive and significant influence between live streaming on impulsive buying behavior on the Shopee marketplace. The f test shows that there is a positive and significant influence between flash sales and live streaming on impulsive buying behavior on the Shopee marketplace.